2020
DOI: 10.5120/ijca2020919974
|View full text |Cite
|
Sign up to set email alerts
|

Action Research to Improve Students’ Problem-Solving Skills using Social Cognitive Theory and Problem based Learning Strategies

Abstract: The main aim of this action research is to improve the student's technical problem-solving skill to fix and manage different technical problems in higher education Institutes. One of the main reasons for the deterioration of higher education institutions in providing the labour market with qualified professional cadres is keeping academic curricula in the classical frameworks and not develop the curricula to coincide with the technical progress. Solving technical problems has become an urgent need of the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In their investigation of students' thinking about the relationship between a function and its derivatives in a geometric context, Berry and Nyman (2003) found that the use of two educational technologies (a TI-83plus graphing calculator and a calculator based ranger) was helpful in supporting students' understanding of the aforementioned relationship. This finding is consistent with that of Hiyam et al (2019) who used Mathematica, a computerized algebra system, to develop students' ability to make connections between graphs of functions and graphs of the functions' derivatives, among other things. Sari et al (2018) reported on a teaching experiment that used GeoGebra, a dynamic mathematics software, to enhance students' ability to visualize the concept of the derivative.…”
Section: The Role Of Technology In the Teaching Of Derivativessupporting
confidence: 87%
See 3 more Smart Citations
“…In their investigation of students' thinking about the relationship between a function and its derivatives in a geometric context, Berry and Nyman (2003) found that the use of two educational technologies (a TI-83plus graphing calculator and a calculator based ranger) was helpful in supporting students' understanding of the aforementioned relationship. This finding is consistent with that of Hiyam et al (2019) who used Mathematica, a computerized algebra system, to develop students' ability to make connections between graphs of functions and graphs of the functions' derivatives, among other things. Sari et al (2018) reported on a teaching experiment that used GeoGebra, a dynamic mathematics software, to enhance students' ability to visualize the concept of the derivative.…”
Section: The Role Of Technology In the Teaching Of Derivativessupporting
confidence: 87%
“…A number of studies have reported promising results related to the integration of technology in the teaching of derivatives in calculus (cf. Berry & Nyman, 2003;Haciomeroglu & Andreasen, 2013;Hiyam et al, 2019;Rosly et al, 2020;Sari et al, 2018;Tall et al, 2008). Other educational technologies that have been used successfully in other studies to enhance students' learning about various calculus ideas including the derivative include MATLAB, Maple, and WolframAlpha, graphing calculators (cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All the semi-primes with 16 digits and below can be factorized in just a matter of seconds using powerful online mathematical software such as Wolfram|Alpha [14][15]. This is independent of the in-built factorization algorithm that this software already uses.…”
Section: Introductionmentioning
confidence: 99%